RESUME OF “THE BASQUE COOPERATIVE LAW IN THE CONTEXT OF INTERNATIONAL COOPERATIVE LAW" - Ruiz, Aingeru (International Journal of Cooperative Law, 2024)
"The Basque Cooperative Law in the Context of International Cooperative Law" is an in-depth analysis of the evolution and significance of cooperative legislation in the Basque Country within a global context. Coordinated by experts in cooperative law, the book explores how the Basque Cooperative Law 11/2019 aligns with international trends in cooperative law and how it can serve as a model for other jurisdictions.